A high-toughness flame-retardant PHA / plant fiber composite material and preparation method thereof

By adding modified polyurethane, sulfur-containing carbon nanotubes and epoxy nanosilica to the PHA/plant fiber composite material, the preparation is blended and prepared, and the shortcomings of existing materials in tensile performance and flame retardant effect are solved, and a high-toughness and flame retardant PHA/plant fiber composite material is achieved.

CN119735932APending Publication Date: 2025-04-01NINGBO HOMELINK ECO ITECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411941027.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing PHA/plant fiber composites have shortcomings in tensile properties and flame retardant effects, and it is difficult to meet the needs of high toughness and flame retardant.

Method used

Highly tough and flame-retardant PHA/plant fiber composite material was prepared by blending polyhydroxy fatty acid esters, rice husk powder, bamboo powder, white carbon black, antioxidant 168, polypropylene wax, modified polyurethane, sulfur-containing carbon nanotubes and epoxy nanosilica in a twin-screw extruder.

Benefits of technology

The material has high toughness and good flame retardant effect, the tensile performance reaches 40.5-427MPa, and the limit oxygen index reaches 131.4V-0, which significantly improves the material's mechanical properties and flame retardant properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the field of material technology, and discloses a high-toughness flame-retardant PHA / plant fiber composite material and a preparation method thereof. The present invention is provided by adding polyhydroxyalkanoate, rice husk powder, bamboo powder, white carbon black, antioxidant 168, polypropylene wax, modified polyurethane, sulfur-containing carbon nanotubes, and epoxy nano-silicon dioxide into a twin-screw extruder, and the blending temperature is 180-190°C, and the extrusion temperature is 170-180°C, to obtain a high-toughness flame-retardant PHA / plant fiber composite material. During extrusion, the epoxy groups in epoxy nano-silicon dioxide react with the hydroxyl groups in the modified polyurethane, sulfur-containing carbon nanotubes, rice husk powder, and bamboo powder, thereby increasing the compatibility with each other, and closely cross-linking is produced with each other, and further entangled with the polyhydroxyalkanoate to form an inorganic-organic hybrid structure, thereby increasing its mechanical properties. The phosphorus element and the sulfur element in the modified polyurethane and the sulfur-containing carbon nanotubes have a good flame retardant effect, and are synergistically flame retardant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a high-toughness and flame-retardant PHA / plant fiber composite material and a preparation method thereof. Background Art

[0002] Polyhydroxyalkanoates (PHA) are a type of biodegradable polyester synthesized by microorganisms, with a variety of excellent properties and broad application prospects, but PHA itself has relatively poor strength and toughness, so how to avoid this phenomenon is the key to solving the problem. Plant fibers have toughness, so they are blended with PHA to improve their performance. For example, patent CN106192202B discloses a plant composite fiber, a plant fiber flame-retardant composite material, and a method for preparing a plant fiber flame-retardant composite material. The plant fiber flame-retardant composite material in this invention can be widely used in packaging products, handicrafts, daily necessities and other fields; however, its tensile and flame-retardant effects have not been improved. Summary of the invention

[0003] 1. Technical issues to be solved

[0004] In view of the deficiencies of the prior art, the present invention provides a high-toughness flame-retardant PHA / plant fiber composite material and a preparation method thereof, which has good flame retardancy and tensile strength.

[0005] (II) Technical solution

[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a high-toughness flame-retardant PHA / plant fiber composite material, comprising the following components by weight: 40-75 parts by weight of polyhydroxyalkanoate, 20-30 parts by weight of rice husk powder, 10-16 parts by weight of bamboo powder, 1-2 parts by weight of white carbon black, 0.2-0.6 parts by weight of antioxidant 168, 0.3-0.4 parts by weight of polypropylene wax, 5-8 parts by weight of modified polyurethane, 4-6 parts by weight of sulfur-containing carbon nanotubes, and 2-4 parts by weight of epoxy nano-silica.

[0007] Preferably, the preparation method of the modified polyurethane is:

[0008] (1) Under a nitrogen atmosphere, 2,6-dialdehyde-1,5-dihydroxynaphthalene and 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone are added to an ethanol solvent, stirred to dissolve, and stirred to react at 70-90° C. for 6-10 hours. After the reaction, the mixture is filtered while hot, washed with ethanol, and dried to obtain an intermediate 1;

[0009] (2) adding DOPO to N,N-dimethylformamide solvent, introducing nitrogen protection, stirring evenly, and then adding intermediate 1, reacting at 60-85° C. for 7-9 hours, and then distilling under reduced pressure, washing and drying to obtain a phosphorus-containing chain extender;

[0010] (3) dissolving 15-25 parts by weight of polylactic acid in dichloromethane, adding 1.6-1.9 parts by weight of dicyclohexylcarbodiimide and 1-1.2 parts by weight of N-hydroxysuccinimide, activating for 2-4 hours at 2-5° C. in a nitrogen atmosphere, then adding 10-14 parts by weight of ethylenediamine, reacting for 18-30 hours at 20-40° C., adding ethanol to precipitate after the reaction, filtering the solvent, washing with ethanol, and obtaining an amino polylactic acid chain extender;

[0011] (4) After removing water from the polyether diol, mix it evenly with hexamethylene diisocyanate, introduce nitrogen, then drop dibutyltin dilaurate as a catalyst, react at 50-80° C. for 2-4 hours to carry out prepolymerization, then add a phosphorus-containing chain extender, stir to continue the chain extension reaction, react at 50-60° C. for 1-2 hours, and after completion, cool and discharge to obtain a modified polyurethane.

[0012] Preferably, the mass ratio of 2,6-dialdehyde-1,5-dihydroxynaphthalene to 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone in (1) is 1:0.9-1.2.

[0013] Preferably, the mass ratio of DOPO to intermediate 1 in (2) is 2.1-2.3:1.

[0014] Preferably, the mass ratio of the polyether diol, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, phosphorus-containing chain extender, and amino polylactic acid chain extender in (4) is 1.2-1.3:1:0.01-0.03:0.5-0.7:0.4-0.5.

[0015] Preferably, the preparation method of the sulfur-containing carbon nanotubes is:

[0016] S1. Add 4-6 parts by weight of vinyl carbon nanotubes to N,N-dimethylformamide solvent, ultrasonically disperse for 10-15 minutes, then continue to add 5-14 parts by weight of mercaptoethylamine and 1-1.3 parts by weight of benzoin dimethyl ether initiator, irradiate with 365nm ultraviolet light at 45-55°C for 2-3h, centrifuge, wash and dry after completion to obtain intermediate 2;

[0017] S2. Add intermediate 2 and phosphorus-containing chain extender into N,N-dimethylformamide solvent, stir and mix, continue to add p-toluenesulfonic acid catalyst, carry out esterification reaction, react at 85-100°C for 7-12h, and then distill under reduced pressure, wash and dry to obtain sulfur-containing carbon nanotubes.

[0018] Preferably, the mass ratio of the intermediate 2, the phosphorus-containing chain extender, and the p-toluenesulfonic acid catalyst in S2 is 1:0.8-1.1:0.01-0.03.

[0019] Preferably, the preparation method of the high-toughness flame-retardant PHA / plant fiber composite material is: adding polyhydroxyalkanoate, rice husk powder, bamboo powder, white carbon black, antioxidant 168, polypropylene wax, modified polyurethane, sulfur-containing carbon nanotubes, and epoxy nano-silica into a twin-screw extruder, with a blending temperature of 180-190°C and an extrusion temperature of 170-180°C to obtain a high-toughness flame-retardant PHA / plant fiber composite material. (III) Beneficial Technical Effects

[0020] The invention obtains a high-toughness flame-retardant PHA / plant fiber composite material by adding polyhydroxyalkanoate, rice husk powder, bamboo powder, white carbon black, antioxidant 168, polypropylene wax, modified polyurethane, sulfur-containing carbon nanotubes and epoxy nano-silica into a twin-screw extruder at a blending temperature of 180-190° C. and an extrusion temperature of 170-180° C.

[0021] During the extrusion process, the epoxy groups in the epoxy nano-silica will undergo a ring-opening reaction with the hydroxyl groups in the modified polyurethane, sulfur-containing carbon nanotubes, rice husk powder, and bamboo powder, increasing their compatibility and reducing the agglomeration of the epoxy nano-silica and carbon nanotubes. They will be closely cross-linked and further entangled with polyhydroxyalkanoates to form an inorganic-organic hybrid structure, which increases its mechanical properties. The phosphorus and sulfur elements in the modified polyurethane and sulfur-containing carbon nanotubes have good flame retardant effects and synergistic flame retardancy, and the intermediate 2 reacts with the phosphorus-containing chain extender to further increase the degree of substitution of the phosphorus element, making its flame retardant effect better. DETAILED DESCRIPTION

[0022] DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide), CAS number is 35948-25-5.

[0023] The preparation process of vinyl carbon nanotubes refers to the journal "Materials Science and Engineering Plastics" Volume 23, Issue 4, "Surface Vinyl Functionalization of Multi-walled Carbon Nanotubes": 0.3g of multi-walled carbon nanotubes were added to 30mL of 98% concentrated sulfuric acid and 10mL of 70% concentrated nitric acid, refluxed at 140°C for 1h, filtered, and washed. 0.1g of the acidified carbon nanotubes obtained were weighed and dispersed in 15mL of acetone and 15mL of chloroform, 2mL of triethylamine and 5mL of acryloyl chloride were added, and the reaction was carried out at 40°C for 24h. Then 10mL of ethanol was added and stirred for 2h, filtered, and washed to obtain vinyl carbon nanotubes.

[0024] Preparation of epoxy nano-silica: Referring to the literature "Nano-silica modified with silane coupling agent KH-560", a certain amount of nano-silica was weighed and added to 20 mL of toluene. Ultrasonic dispersion was performed for 30 min at room temperature using a KQ-300E ultrasonic cleaner (300 W) to obtain a uniform suspension. Silane coupling agent KH-560 was then added and ultrasonic dispersion was continued for 3-4 min. The suspension was transferred to a 100 mL four-necked flask equipped with a reflux condenser and a power-enhanced electric stirrer and stirred in an oil bath at a set temperature for reaction. The slurry after the reaction was centrifuged at room temperature at a speed of 12000 r / min using a CT15RT desktop high-speed refrigerated centrifuge to obtain epoxy nano-silica.

[0025] Example 1

[0026] (1) Under a nitrogen atmosphere, 2,6-dialdehyde-1,5-dihydroxynaphthalene and 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone were added to an ethanol solvent, wherein the mass ratio of 2,6-dialdehyde-1,5-dihydroxynaphthalene to 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone was 1:0.9, stirred and dissolved, stirred and reacted at 70° C. for 6 h, filtered while hot after the reaction, washed with ethanol, and dried to obtain an intermediate 1;

[0027] (2) adding DOPO to N,N-dimethylformamide solvent, introducing nitrogen protection, stirring evenly, and then adding intermediate 1, wherein the mass ratio of DOPO to intermediate 1 is 2.1:1, reacting at 60° C. for 7 h, and then distilling under reduced pressure, washing and drying to obtain a phosphorus-containing chain extender;

[0028] (3) dissolving 15 parts by weight of polylactic acid in dichloromethane, adding 1.6 parts by weight of dicyclohexylcarbodiimide and 1 part by weight of N-hydroxysuccinimide, activating at 2° C. for 2-4 hours in a nitrogen atmosphere, then adding 10 parts by weight of ethylenediamine, reacting at 20° C. for 18 hours, adding ethanol to precipitate after the reaction, filtering the solvent, washing with ethanol, and obtaining an amino polylactic acid chain extender;

[0029] (4) After removing water from the polyether diol, mix it evenly with hexamethylene diisocyanate, introduce nitrogen, then add dibutyltin dilaurate catalyst dropwise, react at 50°C for 2h, perform prepolymerization, and then add a phosphorus-containing chain extender, wherein the mass ratio of polyether diol, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, phosphorus-containing chain extender, and amino polylactic acid chain extender is 1.2:1:0.01:0.5:0.4, stir to continue the chain extension reaction, react at 50°C for 1h, and after completion, cool and discharge to obtain a modified polyurethane.

[0030] (5) Add 4 parts by weight of vinyl carbon nanotubes to N,N-dimethylformamide solvent, and disperse them by ultrasonic for 10 minutes. Then, add 5 parts by weight of mercaptoethylamine and 1 part by weight of benzoin dimethyl ether initiator, and irradiate with 365 nm ultraviolet light at 45° C. for 2 hours. After the reaction, centrifuge, wash and dry to obtain intermediate 2.

[0031] (6) adding intermediate 2 and a phosphorus-containing chain extender to an N,N-dimethylformamide solvent, stirring and mixing, and continuing to add a p-toluenesulfonic acid catalyst, wherein the mass ratio of intermediate 2, phosphorus-containing chain extender, and p-toluenesulfonic acid catalyst is 1:0.8:0.01, and performing an esterification reaction at 85° C. for 7 h. After the reaction, performing reduced pressure distillation, washing, and drying to obtain sulfur-containing carbon nanotubes;

[0032] (7) 40 parts by weight of polyhydroxyalkanoate, 20 parts by weight of rice husk powder, 10 parts by weight of bamboo powder, 1 part by weight of white carbon black, 0.2 parts by weight of antioxidant 168, 0.3 parts by weight of polypropylene wax, 5 parts by weight of modified polyurethane, 4 parts by weight of sulfur-containing carbon nanotubes, and 2 parts by weight of epoxy nanosilica are added into a twin-screw extruder at a blending temperature of 180°C and an extrusion temperature of 170°C to obtain a high-toughness flame-retardant PHA / plant fiber composite material.

[0033] Example 2

[0034] (1) Under a nitrogen atmosphere, 2,6-dialdehyde-1,5-dihydroxynaphthalene and 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone are added to an ethanol solvent, wherein the mass ratio of 2,6-dialdehyde-1,5-dihydroxynaphthalene to 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone is 1:1.2, and after stirring and dissolving, stirring and reacting at 90° C. for 10 hours, filtering while hot after the reaction, washing with ethanol, and drying to obtain intermediate 1;

[0035] (2) adding DOPO to N,N-dimethylformamide solvent, introducing nitrogen protection, stirring evenly, and then adding intermediate 1, wherein the mass ratio of DOPO to intermediate 1 is 2.3:1, reacting at 85° C. for 9 h, and then distilling under reduced pressure, washing and drying to obtain a phosphorus-containing chain extender;

[0036] (3) dissolving 25 parts by weight of polylactic acid in dichloromethane, adding 1.9 parts by weight of dicyclohexylcarbodiimide and 1.2 parts by weight of N-hydroxysuccinimide, activating at 5° C. for 4 h in a nitrogen atmosphere, then adding 14 parts by weight of ethylenediamine, reacting at 40° C. for 30 h, adding ethanol to precipitate after the reaction, filtering the solvent, washing with ethanol, and obtaining an amino polylactic acid chain extender;

[0037] (4) removing water from the polyether diol and mixing it evenly with hexamethylene diisocyanate, introducing nitrogen, then dropping a dibutyltin dilaurate catalyst, reacting at 80° C. for 4 hours, performing prepolymerization, and then adding a phosphorus-containing chain extender, wherein the mass ratio of the polyether diol, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, phosphorus-containing chain extender, and amino polylactic acid chain extender is 1.3:1:0.03:0.7:0.5, stirring to continue the chain extension reaction, reacting at 60° C. for 2 hours, and after completion, cooling and discharging to obtain a modified polyurethane;

[0038] (5) Add 6 parts by weight of vinyl carbon nanotubes to N,N-dimethylformamide solvent, and disperse them by ultrasonication for 15 minutes. Then, add 14 parts by weight of mercaptoethylamine and 1.3 parts by weight of benzoin dimethyl ether initiator. Irradiate with 365 nm ultraviolet light at 55° C. for 3 hours. After the reaction, centrifuge, wash and dry to obtain intermediate 2.

[0039] (6) adding intermediate 2 and a phosphorus-containing chain extender to an N,N-dimethylformamide solvent, stirring and mixing, and continuing to add a p-toluenesulfonic acid catalyst, wherein the mass ratio of intermediate 2, phosphorus-containing chain extender, and p-toluenesulfonic acid catalyst is 1:1.1:0.03, and performing an esterification reaction at 100° C. for 12 h. After completion, performing reduced pressure distillation, washing, and drying to obtain sulfur-containing carbon nanotubes;

[0040] (7) 75 parts by weight of polyhydroxyalkanoate, 30 parts by weight of rice husk powder, 16 parts by weight of bamboo powder, 2 parts by weight of white carbon black, 0.6 parts by weight of antioxidant 168, 0.4 parts by weight of polypropylene wax, 8 parts by weight of modified polyurethane, 6 parts by weight of sulfur-containing carbon nanotubes, and 4 parts by weight of epoxy nano-silica are added into a twin-screw extruder at a blending temperature of 190° C. and an extrusion temperature of 180° C. to obtain a high-toughness flame-retardant PHA / plant fiber composite material.

[0041] Example 3

[0042] (1) Under a nitrogen atmosphere, 2,6-dialdehyde-1,5-dihydroxynaphthalene and 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone were added to an ethanol solvent, wherein the mass ratio of 2,6-dialdehyde-1,5-dihydroxynaphthalene to 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone was 1:1.1, stirred and dissolved, stirred and reacted at 80° C. for 8 h, filtered while hot after the reaction, washed with ethanol, and dried to obtain intermediate 1;

[0043] (2) adding DOPO to N,N-dimethylformamide solvent, introducing nitrogen protection, stirring evenly, and then adding intermediate 1, wherein the mass ratio of DOPO to intermediate 1 is 2.2:1, reacting at 72° C. for 8 h, and then distilling under reduced pressure, washing and drying to obtain a phosphorus-containing chain extender;

[0044] (3) dissolving 20 parts by weight of polylactic acid in dichloromethane, adding 1.7 parts by weight of dicyclohexylcarbodiimide and 1 part by weight of N-hydroxysuccinimide, activating at 3° C. for 2 h in a nitrogen atmosphere, then adding 12 parts by weight of ethylenediamine, reacting at 30° C. for 25 h, adding ethanol to precipitate after the reaction, filtering the solvent, washing with ethanol, and obtaining an amino polylactic acid chain extender;

[0045] (4) removing water from the polyether diol and mixing it evenly with hexamethylene diisocyanate, introducing nitrogen, then dropping a dibutyltin dilaurate catalyst, reacting at 70° C. for 3 hours, performing prepolymerization, and then adding a phosphorus-containing chain extender, wherein the mass ratio of the polyether diol, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, phosphorus-containing chain extender, and amino polylactic acid chain extender is 1.2:1:0.02:0.6:0.45, stirring to continue the chain extension reaction, reacting at 55° C. for 1 hour, and after completion, cooling and discharging to obtain a modified polyurethane;

[0046] (5) Add 5 parts by weight of vinyl carbon nanotubes to N,N-dimethylformamide solvent, and disperse them by ultrasonic for 13 minutes. Then, add 8 parts by weight of mercaptoethylamine and 1.2 parts by weight of benzoin dimethyl ether initiator, and irradiate with 365 nm ultraviolet light at 50° C. for 2 hours. After the reaction, centrifuge, wash and dry to obtain intermediate 2.

[0047] (6) adding intermediate 2 and a phosphorus-containing chain extender to an N,N-dimethylformamide solvent, stirring and mixing, and continuing to add a p-toluenesulfonic acid catalyst, wherein the mass ratio of intermediate 2, phosphorus-containing chain extender, and p-toluenesulfonic acid catalyst is 1:0.9:0.02, and performing an esterification reaction at 95° C. for 10 h. After the reaction, performing reduced pressure distillation, washing, and drying to obtain sulfur-containing carbon nanotubes;

[0048] (7) 60 parts by weight of polyhydroxyalkanoate, 25 parts by weight of rice husk powder, 13 parts by weight of bamboo powder, 1 part by weight of white carbon black, 0.4 parts by weight of antioxidant 168, 0.3 parts by weight of polypropylene wax, 6 parts by weight of modified polyurethane, 5 parts by weight of sulfur-containing carbon nanotubes, and 3 parts by weight of epoxy nanosilica are added into a twin-screw extruder at a blending temperature of 185°C and an extrusion temperature of 175°C to obtain a high-toughness flame-retardant PHA / plant fiber composite material.

[0049] Comparative Example 1

[0050] The difference between this comparative example and Example 3 is that no modified polyurethane is added.

[0051] Comparative Example 2

[0052] The difference between this comparative example and Example 3 is that no sulfur-containing carbon nanotubes are added.

[0053] The tensile properties of the material were tested using an electronic universal testing machine. The test results are shown in Table 1.

[0054] Table 1: Tensile properties tested.

[0055] project Tensile properties (MPa) Example 1 40.5 Example 2 42.7 Example 3 41.9 Comparative Example 1 22.3 Comparative Example 2 21.6

[0056] As can be seen from Table 1, the tensile properties of the high-toughness flame-retardant PHA / plant fiber composite material of the present invention reach 40.5-427 MP, indicating that it has good tensile properties and therefore good mechanical properties.

[0057] The limiting oxygen index of the material was tested using an oxygen index meter, and the combustion grade of the material was tested using a horizontal and vertical combustion instrument. The test results are shown in Table 2.

[0058] Table 2: Flame retardancy test.

[0059] Group Limiting oxygen index (%) Combustion level Example 1 31.4 V-0 Example 2 32.7 V-0 Example 3 30.5 V-0 Comparative Example 1 21.4 V-1 Comparative Example 2 20.3 V-1

[0060] It can be seen from Table 2 that Examples 1-3 of the present invention have better flame retardant effects than Comparative Examples 1-2.

[0061] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high-toughness flame-retardant PHA / plant fiber composite material, characterized in that: The invention comprises the following components by weight: 40-75 parts by weight of polyhydroxyalkanoate, 20-30 parts by weight of rice husk powder, 10-16 parts by weight of bamboo powder, 1-2 parts by weight of white carbon black, 0.2-0.6 parts by weight of antioxidant 168, 0.3-0.4 parts by weight of polypropylene wax, 5-8 parts by weight of modified polyurethane, 4-6 parts by weight of sulfur-containing carbon nanotubes, and 2-4 parts by weight of epoxy nano-silica; The preparation method of the modified polyurethane is: (1) Under a nitrogen atmosphere, 2,6-dialdehyde-1,5-dihydroxynaphthalene and 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone are added to an ethanol solvent, stirred to dissolve, and stirred to react at 70-90° C. for 6-10 hours. After the reaction, the mixture is filtered while hot, washed with ethanol, and dried to obtain an intermediate 1; (2) adding DOPO to N,N-dimethylformamide solvent, introducing nitrogen protection, stirring evenly, and then adding intermediate 1, reacting at 60-85° C. for 7-9 hours, and then distilling under reduced pressure, washing and drying to obtain a phosphorus-containing chain extender; (3) dissolving 15-25 parts by weight of polylactic acid in dichloromethane, adding 1.6-1.9 parts by weight of dicyclohexylcarbodiimide and 1-1.2 parts by weight of N-hydroxysuccinimide, activating for 2-4 hours at 2-5° C. in a nitrogen atmosphere, then adding 10-14 parts by weight of ethylenediamine, reacting for 18-30 hours at 20-40° C., adding ethanol to precipitate after the reaction, filtering the solvent, washing with ethanol, and obtaining an amino polylactic acid chain extender; (4) After removing water from the polyether diol, mix it evenly with hexamethylene diisocyanate, introduce nitrogen, then add dibutyltin dilaurate as a catalyst dropwise, react at 50-80° C. for 2-4 hours to perform prepolymerization, then add a phosphorus-containing chain extender and an amino polylactic acid chain extender, stir to continue the chain extension reaction, react at 50-60° C. for 1-2 hours, and after completion, cool and discharge to obtain a modified polyurethane.

2. The high-toughness flame-retardant PHA / plant fiber composite material according to claim 1, characterized in that: The mass ratio of 2,6-dialdehyde-1,5-dihydroxynaphthalene to 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone in (1) is 1:0.9-1.

2.

3. The high-toughness flame-retardant PHA / plant fiber composite material according to claim 1, characterized in that: The mass ratio of DOPO to intermediate 1 in (2) is 2.1-2.3:

1.

4. The high-toughness flame-retardant PHA / plant fiber composite material according to claim 1, characterized in that: The mass ratio of the polyether diol, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, phosphorus-containing chain extender and amino polylactic acid chain extender in (4) is 1.2-1.3:1:0.01-0.03:0.5-0.7:0.4-0.

5.

5. The high-toughness flame-retardant PHA / plant fiber composite material according to claim 1, characterized in that: The preparation method of the sulfur-containing carbon nanotubes is: S1. Add 4-6 parts by weight of vinyl carbon nanotubes to N,N-dimethylformamide solvent, ultrasonically disperse for 10-15 minutes, then continue to add 5-14 parts by weight of mercaptoethylamine and 1-1.3 parts by weight of benzoin dimethyl ether initiator, irradiate with 365nm ultraviolet light at 45-55°C for 2-3h, centrifuge, wash and dry after completion to obtain intermediate 2; S2. Add intermediate 2 and phosphorus-containing chain extender into N,N-dimethylformamide solvent, stir and mix, continue to add p-toluenesulfonic acid catalyst, carry out esterification reaction, react at 85-100°C for 7-12h, and then distill under reduced pressure, wash and dry to obtain sulfur-containing carbon nanotubes.

6. The high-toughness flame-retardant PHA / plant fiber composite material according to claim 5, characterized in that: The mass ratio of the intermediate 2, the phosphorus-containing chain extender and the p-toluenesulfonic acid catalyst in S2 is 1:0.8-1.1:0.01-0.

03.

7. A method for preparing a high-toughness flame-retardant PHA / plant fiber composite material according to any one of claims 1 to 6, characterized in that: The preparation method of the high-toughness flame-retardant PHA / plant fiber composite material is as follows: polyhydroxyalkanoate, rice husk powder, bamboo powder, white carbon black, antioxidant 168, polypropylene wax, modified polyurethane, sulfur-containing carbon nanotubes, and epoxy nano-silica are added into a twin-screw extruder, the blending temperature is 180-190° C., and the extrusion temperature is 170-180° C., so as to obtain the high-toughness flame-retardant PHA / plant fiber composite material.

Citation Information

Patent Citations

  • A method for preparing plant composite fibers, plant fiber composite materials, and plant fiber composite materials.

    CN106192202B